First identification of Curvularia xishuangbannaensis Tibpromma &K.D. Hyde, sp. nov as a causal agent of leaf spot in oil palm nurseries andevaluation of fungicidal efficacy - Amrutha Lakshmi, M; Arutselvan, R; Indraja, M; Challa, G K; Ramachandrudu, K (Journal of Horticultural Sciences, 2025)
Leaf spot caused by Curvularia spp. represents a major constraint in oil palm nurseries, adversely affecting plant health and productivity. This study reports the first identification of Curvularia xishuangbannaensis as the causal agent of oil palm leaf spot, confirmed through colony and spore morphology, ITS-based molecular phylogenetic analysis, and pathogenicity testing using the disc placement method. The in vitro evaluation of fourteen fungicides using the poisoned food technique revealed complete inhibition of mycelial growth by eight fungicides across all tested concentrations, including azoxystrobin 8.3% + mancozeb 66.6% WDG, propiconazole 25% EC, hexaconazole 5% SC, difenconazole 25% EC, triflumizole, tebuconazole 25.9% EC, propiconazole 13.9% + difenconazole 13.9%, and flupyram 17.7% + tebuconazole 11.4% SC. To date, no reports exist on Curvularia species causing leaf spot in oil palm in India or systematic fungicide evaluations against this pathogen. These findings enhance understanding of the pathogenicity of C. xishuangbannaensis and support effective disease management strategies in oil palm nurseries.